Enhancing Food Biotechnology Literacy through Informal Science Learning of Mozzarella Cheese-Making Workshop: A Case Study - Tiffany Safitri; Indriyani Rachman; Surti Kurniasih (Jurnal Pemberdayaan Masyarakat, 2025)
Biotechnology-based food processing holds strong potential to empower rural and peri-urban communities by enhancing local knowledge and skills. However, limited public understanding of its principles remains a significant challenge. This study aimed to evaluate the effectiveness of a community empowerment program focused on homemade cheese-making using biotechnology concepts. The activity was conducted through a hands-on workshop involving 20 participants aged 11–50 years, incorporating pretests and posttests to assess knowledge improvement, observation sheets to monitor engagement, and participant questionnaires. The results showed a high level of effectiveness, with an average normalized gain score of 0.78, indicating substantial improvement in understanding basic biotechnology. Feedback indicated that participants enjoyed the activity, gained confidence in applying the methods at home, and expressed interest in further food science workshops. The empowerment program facilitated not only science literacy but also community innovation, as seen in the use of household materials and local ingredients such as milk from nearby dairy farms. This study demonstrates that informal, context-based science education can successfully bridge knowledge gaps while fostering active participation. It suggests that similar initiatives focused on fermentation-based products may serve as a sustainable approach to community-based science learning and rural development.